The Effect of Mastery of Technology and Financial Literacy on Accounting Student Competencies - Tamba, Rani Rosya; Tsamara Nayla Safitri; Panjaitan, Gloria Oktavania; Nada Syifa Athaya; Wan Fachrudin (International Journal of Economic Research and Financial Accounting, 2025)
The purpose of this study is to find out how technology mastery and financial knowledge of students at Universitas Pembangunan Panca Budi in Medan affect their accounting skills. The study involved 36 students who were randomly selected from a population of 233 students. Data was collected through an online questionnaire and analyzed using SPSS version 23. The findings revealed that financial knowledge significantly influences accounting competencies (t-value = 5.546, p < 0.05), while technology mastery does not have a significant effect (t-value = 0.276, p > 0.05). Simultaneously, both variables influence accounting competencies (F-value = 17.658, p < 0.05), with financial literacy being the dominant factor. These results underscore the importance of financial knowledge in enhancing accounting education.